Drying kinetics and effect of air-drying temperature on chemical composition of Phyllanthus amarus and Phyllanthus niruri. Issue 5 (4th April 2018) - Sousa, Adriana Dutra; Ribeiro, Paulo Riceli Vasconcelos; Canuto, Kirley Marques; Zocolo, Guilherme Julião; Pereira, Rita de Cassia Alves; Fernandes, Fabiano André Narciso; Sousa de Brito, Edy
ABSTRACT: In this study, the drying kinetics of Phyllanthus amarus and Phyllanthus niruri were investigated experimentally in an air-drying oven as a function of drying temperature (50, 60, and 70°C). The effects of the air-drying temperature on the phenolic content and the LC–MS profile were also studied. Increases in air-drying temperature reduced the drying time and increased the effective moisture diffusivity. An Arrhenius relationship with activation energy values of 22.828 and 43.129 kJ/mol for P. niruri and P.amarus, respectively, expressed the effect of temperature on the diffusivity. Air drying at 70°C increased the availability of some phenolic compounds. However, the higher temperature negatively affected some sensitive components.